Experimental Thermal Hazard Investigation of Pressure and EC/PC/EMC Mass Ratio on Electrolyte - Changcheng Liu; Kaihui Zheng; Yong Zhou; Kai Zhu; Que Huang (Energies, 2021)
Electrolytes are involved in the thermal runaway (TR) process of cells, which is a potential hazard in lithium-ion batteries (LIBs). Therefore, the effects of different mass ratio of carbonate solvents (ethylene carbonate (EC)/propylene carbonate (PC)/ethyl methyl carbonate (EMC)) with LiBF4 and different environmental pressure on the combustion characteristics of electrolyte such as flame centerline temperature, mass loss rate (MLR) and heat release rate (HRR) were analyzed. The combustion process could be divided into four stages: ignition, stable combustion stage, stable combustion with flame color change stage and extinguishing; with the decrease of pressure, the MLR of electrolyte declined and the combustion time prolonged, while the temperature of flame centerline increased.